Revisión de epicondilitis: clínica, estudio y propuesta de protocolo de tratamiento - Miranda M., Ana Luisa; Llanos V., Natalia; Torres B., Carlos; Montenegro S., Constanza; Jiménez, Catalina (Revista Hospital Clínico Universidad de Chile, 2010)
Epicondylitis is characterized by pain localized in the insertion of the elbow`s epicondilar muscles, resulting from traumatic inflammation caused by repetitive pronation-supination`s movements. It is known that early conservative treatment is the key toresolution of symptoms. However, 5 to 10% of patients are not responsive to medical treatment. After reviewing the literature and based on the best available evidence, we have prepared treatment protocols for acute and chronic epicondylitis. In the acuteepicondylitis approach, the algorithm provides, initially, correction of biomechanical conditions, changes in the patient`s daily activities, use of NSAIDs and Brace. If symptoms persist, corticosteroids infiltration is suggested, in addition to physical therapy andphysiotherapy. In the chronic condition, an integral treatment is recommended, and includes the following: Confirmation of diagnosis and complementation of the medical history with a thorough assessment of pain (DN4 questionnaire); individualized analgesiaconsidering personal risk factors, severity and characteristics of pain; management with local infiltrations; mental health assessment and management of a posible comorbid myofascial syndrome. If the condition does not improve, an advance management isproposed. Finally, suggestions for a successful job reinstatement are made.